Principles, methods & techniques of teaching - Aggarwal, J.C. (New Delhi : Vikas publishing, 2007)
About author(s) j c aggarwal started his career as a lecturer in a teachers? Training college in 1954 and thereafter worked in different positions in the delhi administration. He retired as deputy director of education/executive director of delhi bureau of textbooks. Singly or jointly he has authored some 150 books on education, history and current affairs. He has written some books in education.
Includes index.
Keywords: Principles, methods & techniques of teaching; Teaching; Educational innovations